Caring for Elderly People with Severe Conditions: Do Religious Education and Values Make a Difference? - Lluis Oviedo; Josefa Torralba; Jose Luis Ripoll (Religions, 2022)
Western societies are experiencing a demographic shift towards an increased elderly population that is often affected by limiting conditions. This growth is not always balanced by a greater concern and assistance from younger cohorts, which could perceive that demand as a heavy burden, especially under conditions where children often move to work far away from their families. The present research tries to understand this challenging situation by studying the attitudes of preadolescents and adolescents towards the elderly. This study has explored the reactions of students between 12 and 17 years old towards images and experiences around the oldest and most frail. The collected data indicate the positive role of religion and spirituality in their concern, and the moderating factor of empathy, with gender and age being less significant in their attitudes towards the elderly in their social environment.